Diseño de un sistema de gestión de inocuidad alimentaria para la producción de granola en la industria de cereales Protein Quito - Ecuador de acuerdo a la norma INEM - ISO 22000:2006 - Palacios Sanguano, Evelyn Pamela (2015)
The aim of this study was to design a food safety system for the production of granola cereal industry "protein" Quito - Ecuador according to INEN standard - ISO 22000: 2006. A situational analysis of the industry was established considering the safety parameters of the manufacturing process established in the rules INEN, to be established the process diagram, in which the critical control points are determined and therefore could produce the necessary documentation the establishment of the system of food safety required by the Ministry of Health, and in accordance with the Resolution of the National Quality System published in Official Register No. 839 of November 27, 2012 in which to be established compliance policies and a maximum of four years for the implementation of food control systems in the Ecuadorian industries. Through the situational analysis to "PROTEIN" met different faults in both the manufacturing process and cleaning the areas of operation, so it saw the need for making of manual and procedures meets the established by the regulations the Standards of Good Manufacturing Practices, Hazard Analysis and Critical Control Points and Standard Operating Procedures of Sanitation, which focuses on the use of the INEN-ISO 22000:2006. "PROTEIN" obtained a compliance rate of 25.45%, partial performance of 20% and the default rate of 54.54%. So we conclude that this system of food safety is a basic tool for the industry. And it is recommended for the “PROTEIN” industry to implement this food safety system to improve production of granola, under those norms.